2018
DOI: 10.1093/ndt/gfy282
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C beta deficiency increases glucose-mediated peritoneal damage via M1 macrophage polarization and up-regulation of mesothelial protein kinase C alpha

Abstract: PKCβ as the dominant PKC isoform in MPMΦ is up-regulated by HG PD fluid and exerts anti-inflammatory effects during PD through regulation of MPMΦ M1/M2 polarization and control of the dominant mesothelial PKC isoform α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
4
14
0
Order By: Relevance
“…Both in murine (MPMCs) and in human peritoneal mesothelial cells (HPMCs), dapagliflozin reduced MCP-1 release in a high-glucose milieu, while it had no effect in normal glucose conditions ( Figure 6C). Consistent with our previous findings, mesothelial cells increased MCP-1 production in response to high glucose, while murine macrophages produced less, possibly reflecting a shift to M2 polarization under high-glucose conditions [13]. Similarly, dapagliflozin administered in normal glucose conditions reduced MCP-1 release but had no further effect in high-glucose conditions.…”
Section: Dapagliflozin Abrogates Proinflammatory Signaling In Murine supporting
confidence: 90%
See 1 more Smart Citation
“…Both in murine (MPMCs) and in human peritoneal mesothelial cells (HPMCs), dapagliflozin reduced MCP-1 release in a high-glucose milieu, while it had no effect in normal glucose conditions ( Figure 6C). Consistent with our previous findings, mesothelial cells increased MCP-1 production in response to high glucose, while murine macrophages produced less, possibly reflecting a shift to M2 polarization under high-glucose conditions [13]. Similarly, dapagliflozin administered in normal glucose conditions reduced MCP-1 release but had no further effect in high-glucose conditions.…”
Section: Dapagliflozin Abrogates Proinflammatory Signaling In Murine supporting
confidence: 90%
“…Because dapagliflozin is easily soluble in aqueous solution, no vehicle was necessary. On the last day of experiments, functional analysis of the PM was performed via ultrafiltration and an equilibration test, and peritoneal effluents were sampled as previously described [4,13]. Thereafter, tissue samples were collected from the anterior abdominal wall for histological and immunofluorescence analysis.…”
Section: Peritoneal Dialysis Fluid Exposure Model In Micementioning
confidence: 99%
“…In the early stages, the adverse effects of high glucose on peritoneal tissue are manifested in its induced cellular oxidative damage and mitochondrial dysfunction . High glucose peritoneal dialysate induces ROS production in peritoneal MCs, which promotes macrophage polarization to aggravate peritoneal mesothelial injury . And it has been reported that hydrogen can regulate ROS activation in macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…22 High glucose peritoneal dialysate induces ROS production in peritoneal MCs, which promotes macrophage polarization to aggravate peritoneal mesothelial injury. 23 And it has been reported that hydrogen can regulate ROS activation in macrophages. 24 Our research shows that molecular hydrogen significantly attenuated high glucose-induced mitochondrial membrane destruction in peritoneal MCs and reduced intracellular ROS production, consistent with the findings of studies on hydrogen effects on cerebral ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…The cell lines were identified by the typical cobblestone morphology of confluent monolayers and by positive staining for E-cadherin, ZO-1, α-SMA, and pan-cytokeratin after 3-day culture at 37 °C without interferon gamma (non-permissive conditions). Primary preitoneal mouse macrophages were isolated from uPAR-/-mice as described previously36 .Raw 264.7 mouse macrophage cell line was from ATCC and cultivated as recommended by the supplier. HK-2 human kidney proximal tubule epithelial cells were from ATCC and cultivated as recommended by the supplier in Keratinocyte Serum Free Medium containing 0.05 mg/ml bovine pituitary extract and 5 ng/ml EGF.Mesothelial cells were transfected using PolyPlus transfection reagents accordingly to the manufacturer instructions.…”
mentioning
confidence: 99%